Effect of systemic antibiotic and probiotic therapies as adjuvant treatments of subgingival instrumentation for periodontitis: a randomized controlled clinical study - Ramos, Tatiane Caroline de Souza [UNESP]; Boas, Mariéllen Longo Vilas [UNESP]; Nunes, Camilla Magnoni Moretto [UNESP]; Ferreira, Camila Lopes [UNESP]; Pannuti, Cláudio Mendes; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: This study assessed the efficacy of two adjunct therapies (antibiotic and probiotic) for periodontal treatment based on clinical and immunological parameters in patients with Stage II and III Grade B periodontitis. METHODOLOGY: 45 patients were randomly allocated into three groups: control group (CG); antibiotic group (GAtb), in which 500 mg amoxicillin + 400 mg metronidazole were used; and probiotic group (GProb), for which Lactobacillus reuteri was used. Patients received medications after undergoing periodontal debridement. Clinical and immunological parameters were assessed at baseline, 30 days, and 90 days. RESULTS: All therapies reduced bleeding on probing (BoP) in the evaluated periods, and the GAtb had a greater reduction at 90 days (p=0.03). The GProb group showed better results for plaque index (PI) and gingival recession (GR) compared to the GAtb at 90 days (p=0.0014; p=0.006). The area of inflammation (PISA Index) significantly decreased in all therapies in the evaluated periods. Therapies had no significant differences regarding moderate pockets. The GAtb had a greater reduction in probing depth (PD) for deep pockets (p=0.03) at 90 days and in the number of deep pocket sites at 30 days (p=0.04). The occurrence of adverse effects was commonly reported in the GAtb as a percentage per patient. The GAtb had a significant reduction in the concentration of interleukins IL-1β and IL-8 and an increase in IL-10 and TNF-α. The CG had a reduction in IL-6 and IL-1 β, whereas in the GProb there was no difference. CONCLUSION: After three months, none of the adjuvant therapies provided any additional benefit for subgingival instrumentation.